KERAGAMAN KONSUMSI PANGAN DAN DENSITAS GIZI PADA REMAJA OBESITAS DAN NON OBESITAS - Swamilaksita, Prita Dhyani; Sa’pang, Mertien (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
Obesity is a serious problem in adolescence because it will continue until adulthood. There is a tendency of Indonesia children often consume energy-densed food which is low quality of food choices. This study aims to analyze differences in diversity of food consumption and nutrient density in obese and non obese adolescents. Cross sectional design was used in this study which used 97 adolescent respondents in West Jakarta Junior High School. The method used the nutritional status is the percent of body fat using Bioelectrical Impedance Analysisis (BIA), Individual Dietary Diversity Score (IDDS) to measure food diversity and Nutrient Density using a 2x24 hour Recall. The results showed that there was no difference of food consumption diversity and protein density in both groups with p value = 0,791 and p = 0,366 (p <0,005). While there is a real difference between the energy density of both groups with p = 0.000 (p <0.005). It means that energy density is related to obesity in adolescents. Therefore, good food choice should be disseminated to students and parents in order to meet the nutritional needs of that age.Â Keywords: obesity, nutrition of adolescents, food diversity, nutrient density